ENSEFALOPATI PADA COVID-19 DENGAN MANIFESTASI GANGGUAN PERILAKU DAN KOGNITIF - Reza Stevano; Rocksy Fransisca V Situmeang; Evlyne E Suryawijaya (NEURONA, 2021)
Neurological manifestations of COVID-19 are wide and varied. We report a case of COVID-19-associated encephalopathy with manifestations of behavioral and cognitive changes, seizures, and altered consciousness, in a 47-year-old male previously diagnosed with COVID-19 two weeks prior. Upon physical examination, the patient was found to be agitated and disoriented. The neurological exam was nonfocal. Laboratory tests and a noncontrast head CT revealed normal results, while the nasopharyngeal swab polymerase chain reaction (PCR) was positive. Cerebrospinal fluid (CSF) studies were significant for elevated protein (0.54g/L) with a normal cell and glucose count, and CSF PCR were negative for presence of SARS-CoV-2. The patient received therapy with remdesivir, dexamethasone, heparin, antibiotics, and phenytoin, and was admitted for 8 days with marked improvement. Three weeks later, tests for cognitive function were performed and showed mild deficits in attention and short-term memory. Encephalopathy in COVID-19 can manifest as altered consciousness, seizure, behavioral and cognitive changes. It can emerge even without the presence of known risk factors and occur after the initial acute phase of SARS-CoV-2 infection, which might be due to a persistent immune response as a result of the presence of trace amounts of virus.